Մովսես Խորենացու «Վարդավառի խորհրդի մասին» ճառը որպես աստվածաբանական մտքի հուշարձան - Մաթևոսյան, Արթուր (Ասողիկ հրատ.)
The creative heritage of "the father of the Armenian history" Moses of Khoren always was in the focus of attention of armenologists. however they mainly showed interest in the problems connected with his "History of Armenia". Meanwhile his theological works, which have the considerable value, did not become the subject matter for researchers. In this connection the big interest represents the discourse "On the mystery of the feast of Transfiguration", traditionally ascribed to Moses of Khoren.
Keywords: Հայ գրականություն; Հայոց պատմություն